Madness and the Middle Passage: Warner-Vierya's Juletane as a Paradigm for Writing Caribbean Women's Identities - Ann Elizabeth Willey (Studies in 20th & 21st Century Literature, 1997)
This article links Glissant's theory of an inherent Caribbean madness due to the originary rupture and alienation from Africa with Foucault's theory of the ritual significance and essential liminality of the madman as exemplified in the medieval figure of the "Ship of Fools." In calling the madman the "passenger par excellence," Foucault implies a connection between sanity and linear narratives, such as that of a voyage. Myriam Warner-Vierya's novel, Juletane, suggests that European paradigms of narrative and voyage are inadequate to provide a sense of self for Caribbean women. The novel takes the form of a diary that chronicles the steadily disintegrating marriage and sanity of Juletane, a Caribbean woman orphaned at ten, raised in Paris, who meets and marries an African student in an effort to find a new identity in her husband and a return to Africa. The novel suggests that the linear narrative of a return to the source in Africa denies the rupture with Africa and the immediate circumstances of Caribbean subject-hood. In her efforts, Juletane ignores the alternative narrative possibilities that the novel presents in the circular and shared narratives of women that do not depend on a sense of closure or arrival, but like the voyage of the madman, remain open to the infinite crossroads of the sea and narration.
Keywords: Glissant& #x27; s theory; Glissant; Caribbean madness; Caribbean; rupture; alienation from Africa; alienation; Foucault& #x27; s theory; Foucault; ritual significance; essential liminality; madman; medieval figure; medieval; Ship of Fools; passenger par excellence; sanity; linear narratives; voyage; Myriam Warner-Vierya; Juletane; European paradigms; narrative; inadequate; sense of self; Caribbean women; diary; chronicles; marriage; orphaned; adolescence; Paris; new identity; African; husband; wife; return to Africa; subject-hood; Africa; narrative possibilities; circular narrative; shared narrative; women